THE INFLUENCE OF GROWTH AND SURVIVOR RATE ON TOMATO ANEMONE FISH AMPHIPRION FRENATUS BREVOORT 1856 - Loc, Ha Le Thi; Quynh, Bui Thi Nhu (Vietnam Journal of Marine Science and Technology, 2009)
This study presents data on the effect ofdensity on growth and survival rateofAmphiprion ji-enatus. Four experiments were concluded: 2, 3, 4 and 5 inds/1. As a result, density clearly affected growth and survival rate ofA. ji-enatus. The highest growth and survival rate were achieved on 2 inds/1 (Specific Growth Rate- Length: 0.59%/day, growth rate - length: 26mm respective with survivor rate: 100%) but it is not different ji-om inds which were raised at 3 inds/1 (Specific Growth Rate- Length: 0.55%/day, growth rate length: 25.4mm respective with survival' rate: 100%) (base on statistical analysis). In the 4inds/1 experiment, survival was achieved 100% but growth rate was slower than two experiments before (Specific Growth Rate- Length:0.4%/day, growth rate - length: 24mm respective). The lowest growth and survival were achieved at 5 inds/1 (Specific Growth RateLength: 0.29%/day, growth rate - length: 23mm respective with suvivor rate: 93%). So, if we consider economic effect, we should choose to raise A.frenatus at 3 inds/1.